2012
DOI: 10.7150/ijms.4841
|View full text |Cite
|
Sign up to set email alerts
|

CD44+/CD105+ Human Amniotic Fluid Mesenchymal Stem Cells Survive and Proliferate in the Ovary Long-Term in a Mouse Model of Chemotherapy-Induced Premature Ovarian Failure

Abstract: Objectives: Stem cell transplantation has been reported to rescue ovarian function in a preclinical mouse model of chemotherapy-induced premature ovarian failure (POF); however, maintaining the survival and self-renewal of transplanted seed cells in ovarian tissues over the long-term remains a troublesome issue. In this study we aimed to determine whether the CD44+/CD105+ human amniotic fluid cell (HuAFCs) subpopulation represent potential seed cells for stem cell transplantation treatments in POF. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 22 publications
2
87
0
1
Order By: Relevance
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown in animal models that MSCs from different sources (e.g. adipose) can improve or even restore ovarian function [56][57][58][59]. To determine the ideal age at which POMSCs could be used to regenerate ovaries, the ovarian tissue of more patients at different ages would need to be included.…”
Section: Discussionmentioning
confidence: 99%
“…These patients also exhibit symptoms of the menopause, such as hot flushes, night sweats and vaginal dryness (1)(2)(3)(4)(5). Furthermore, patients with POF are usually infertile due to a lack of mature, healthy follicles or as a result of the remaining follicles not responding to stimulation (1)(2)(3)(4)(5); therefore, POF is also known as primary ovarian insufficiency (1)(2)(3)(4)(5). At present, the number of patients with POF is increasing; however, the factors contributing to POF are largely unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Premature ovarian failure (POF) is a typical pathological disease of the reproductive system in aging females (1)(2)(3)(4)(5). Patients with POF are <40 years old and commonly have the features of amenorrhea, hypoestrogenism and high levels of gonadotrophin (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%